Landscape of ROD9 Island: Functional annotations and biological network of hypothetical proteins in Salmonella enterica. (December 2019) - Soni, Nikita; Swain, Sunil Kumar; Kant, Ravi; Singh, Aditya; Ravichandran, Rahul; Verma, Suresh K; Panda, Pritam Kumar; Suar, Mrutyunjay
Graphical abstract: Highlights: Landscape of ROD9 Island hypothetical proteins characterization using In-silico tools. 17 ROD9 hypothetical proteins have been characterized based on virulence factors. Content rich biological network of ROD9 Island. SEN1005, a hypothetical protein from ROD9 Island is a key factor for causing virulence and its pathogenicity is facilitated by all other hypothetical proteins. Intrinsic molecular properties and atomistic interactions of SEN1005 may be regulated by interactions with T3SS-III secretory pathway. Abstract: Salmonella, an Enterobacteria is a therapeutically important pathogen for the host. The advancement of genome sequencing of S. enterica serovar Enteritidis have identified a distinct ROD9 pathogenic island, imparting virulence. The occurrence of 17 ROD9 hypothetical proteins, necessitates subsequent bioinformatics approach for structural and functional aspects of protein-protein relations or networks in different pathogenic phenotypes express. A collective analysis using predictive bioinformatics tools that includes NCBI-BLASTp and BLAST2GO annotated the motif patterns and functional significance. The VFDB identified 10 virulence proteins at both genomic and metagenomic level. Phylogenetic analysis revealed a divergent and convergent relationship between 17 ROD9 and 41 SP-1 proteins. Here, combining a comprehensive approach from sequence based, motif recognitions, domain identification, virulence ability to structural modelling provides a precise function to ROD9 proteins biological network, for which no experimental information is available.